Progress in learning disabilities. - Myklebust, Helmer R. (New York Grune and Stratton, 1968)
Irregular
Editor: v. 1- H.R. Myklebust.
Keywords: Handicapped children -- Education -- Periodicals; Learning disabilities; Learning Disorders